Incidence and prevalence of diabetes mellitus in the Americas - Barcelo, Alberto (2001)
Reviews published material on the incidence and prevalence of diabetes mellitus in North America, the Caribbean, Central and \n South America. Observes that diabetes is most prevalent among women, low income earners, and the less educated. Views diabetes as a major public health problem in the Americas, and indicates that its prevalence is increasing in some countries. Recommends urgent implementation of diabetes prevention and control programmes.\n